2014
DOI: 10.3109/2000656x.2014.882345
|View full text |Cite
|
Sign up to set email alerts
|

The impact of surgical resident participation in breast reduction surgery – Outcome analysis from the 2005–2011 ACS-NSQIP datasets

Abstract: Breast reduction surgery is a common and effective surgical technique for treating symptomatic macromastia. There is limited data on the impact of resident involvement on outcomes. This study uses the ACS-NSQIP datasets to assess the impact of surgical resident participation in breast reduction surgery. This study reviewed the 2005-2011 ACS-NSQIP databases identifying primary encounters for reduction mammaplasty with CPT code "19318". It characterised surgical complications into three groups: any, major, and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
29
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 37 publications
1
29
0
Order By: Relevance
“…Single-institution studies as well as large, multi-institution studies have analyzed the impact of resident participation after a variety of operations in general, 2,3 vascular, 4,5 oncologic, 6 and breast 7 subspecialties. However, to our knowledge, the impact of resident participation on perioperative outcomes after only complex liver and pancreatic resections has not been studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Single-institution studies as well as large, multi-institution studies have analyzed the impact of resident participation after a variety of operations in general, 2,3 vascular, 4,5 oncologic, 6 and breast 7 subspecialties. However, to our knowledge, the impact of resident participation on perioperative outcomes after only complex liver and pancreatic resections has not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have examined the impact of resident participation and outcomes using this database. Specifically, outcomes after operations in general, 2,3 vascular, 4,5 oncologic, 6 and breast 7 surgeries have been studied and reported. These reports on the impact of resident participation on perioperative outcome have been mixed; some studies show no effect, whereas others have shown a correlation between resident participation and poorer perioperative outcomes.…”
mentioning
confidence: 99%
“…Due to this worry, the medical community has recently started investigating the topic. Studies in general, plastic, orthopedic, urologic, and head and neck surgery have yielded inconsistent results regarding the potentially adverse influence resident participation in surgery has on postoperative outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Within plastic surgery, the impact of resident participation has also been described in non-aesthetic reconstructive surgery as well as reduction mammoplasty. In non-aesthetic reconstructive surgery, residents were reported to have similar complication rates as attendings alone, though resident participation was associated with increased surgical morbidity in reduction mammoplasty [14,15]. The authors sought to characterize the impact of resident participation in outpatient plastic surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of resident participation in plastic surgery has been studied in non-aesthetic plastic surgery, which showed that resident presence had similar complication profiles to attending surgeons alone [14]. However, in breast reduction, resident participation was reported to be associated with increased surgical morbidity [15]. Additionally, unpublished negative opinions regarding resident participation have been anecdotal and based on limited, unreliable information [16].…”
Section: Introductionmentioning
confidence: 99%